Exploring Agricultural Resilience in Volcano-Prone Regions: A Case Study from Mount Merapi, Indonesia - Rozaki, Zuhud; Kamarudin, Mohd Fauzi; Aziz, Ammar Abdul; Senge, Masateru (Universitas Sebelas Maret, 2023)
Mount Merapi, one of Indonesia’s most active and dangerous volcanoes, experienced a devastating eruption in 2010, causing numerous fatalities and widespread damage to homes and land, especially in areas vulnerable to the volcano’s activity. Despite the inherent risks, many farmers continue to cultivate the region’s land. This study examines the resilience of farmers in the Mount Merapi area in light of the persistent volcanic activity. Employing a qualitative methodology, including in-depth interviews and field observations, the research reveals that farmers’ resilience is shaped by their individual experiences and the contributions of government, private sector, and community actors. Long-term residence in the area has equipped farmers with the knowledge and confidence required to navigate the risks and hazards associated with the volcano. Farmers prioritize their safety but also focus on safeguarding their livestock and other essential resources, which are integral to their livelihoods. The local community is instrumental in supporting farmers and residents in disaster-prone zones, while external organizations offer additional advantages to farmers’ lives. The study proposes that a collaborative effort among all stakeholders is essential for maintaining farmers’ livelihoods in areas susceptible to volcanic activity.